Research Progress on New Types of H2TiO3 Lithium-Ion Sieves: A Review - Ying Li; Zhen Yang; Peihua Ma (Metals, 2023)
The advantages of new types of H2TiO3 lithium-ion sieves, including excellent adsorption performance, high-efficiency Li+-ion selectivity, reliable regeneration, environmental friendliness, and easy preparation, have attracted considerable attention. Currently, the prices of lithium carbonate and other related products are rapidly increasing, so the use of H2TiO3 lithium-ion sieves to extract lithium resources in salt lake brine has become a crucial strategy. H2TiO3 lithium-ion sieve is a layered double hydroxide with a 3R1 sequence to arrange oxygen layers. Its adsorption mechanism involves the breaking of surface O-H bonds and the formation of O-Li bonds. This study provides a theoretical basis for developing high-efficiency lithium-ion sieves. This article also summarizes the influencing factors for the synthesis process of H2TiO3, which can seriously influence the adsorption performance, and offers experimental verification for the preparation of H2TiO3 lithium-ion sieves. H2TiO3 lithium-ion sieves prepared from anatase using a reasonable method show the largest adsorption capacity. In addition, effective ways to recycle H2TiO3 are outlined, which provide a guarantee for its industrial application. Finally, this paper summarizes the full text and points out future research directions for H2TiO3 lithium-ion sieves.